SISTEM PENDUKUNG KEPUTUSAN UNTUK MENENTUKAN KOMODITI UNGGULAN PADA DAERAH PENGEMBANGAN AGROINDUSTRI MENGGUNAKAN METODE WEIGHTED PRODUCT (WP) - Gerzon Maulany (AGRICOLA, 2014)
To develop agro-industrial areas is very important to determined right commodity.  We need a basis data to selection right commodity. It was required a decision support system based on several criteria. The objective of this research is to build software to help decision making of suitable commodity for regional agro-industry. The software was built using a computer programming language based on Weighted Product (WP). It was used to assess each alternative to each criterion. Based on Black box and Acceptance testing performance category, the software met the expected functionality of the system and running well